2017
DOI: 10.18632/oncotarget.14724
|View full text |Cite
|
Sign up to set email alerts
|

Significant efficacy and well safety of apatinib in an advanced liver cancer patient: a case report and literature review

Abstract: Apatinib is a novel and highly selective tyrosine kinase inhibitor of vascular endothelial growth factor receptor-2. Previous studies have suggested that apatinib is safe and effective in some solid tumors. We report one case with advanced hepatocellular carcinoma (HCC), who received apatinib combined with transhepatic arterial chemotherapy and embolization (TACE), and chemotherapy respectively. TACE was administered three times once a month, using lipiodol 10ml, oxaliplatin 150mg, and tegafur 1g. The dose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 22 publications
(28 reference statements)
1
27
0
Order By: Relevance
“…Overall, multiple clinical reports have shown that apatinib has a certain effect on advanced liver cancer, 23 lung cancer, 24 ovarian cancer, 25 and other types of malignancy. Nonetheless, there is no clinical research involving a large dataset that reveals its efficacy in malignant solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, multiple clinical reports have shown that apatinib has a certain effect on advanced liver cancer, 23 lung cancer, 24 ovarian cancer, 25 and other types of malignancy. Nonetheless, there is no clinical research involving a large dataset that reveals its efficacy in malignant solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The patient in our study has thus far achieved disease-free status for 12 months. Apatinib has produced promising clinical outcomes in several other types of cancer [ 39 43 ], and has a high binding affinity relative to other anti-angiogenic drugs. For example, apatinib ligand-receptor binding is 10 times greater than that of sorafenib [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apatinib has been proved effective in many solid tumors, such as gastric cancer, breast cancer and non-small-cell lung cancer [ 92 ]. Apatinib might also be an optional agent for HCCs at stage C because the median PFS was more than 8 months and the alpha-fetoprotein level was significantly decreased [ 93 ]. A single-arm phase II trial of second-line axitinib demonstrated that this inhibitor could achieve 42.3% of tumor control at 16 weeks and further study should be performed to combine the biomarker responses [ 94 ].…”
Section: Targeted Therapies For Hccmentioning
confidence: 99%